Attention as a Factor in the School Performance of Adolescents - Milovanović, Radmila B. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
Attention represents a core of cognitive activity, it is an essential element of meaningful information processing and a key factor in self-regulation which is necessary for academic success. Despite this, there is only a small number of studies that examine the relationship between attention and school performance of adolescents. The aim of this research is an attempt to identify the components of attention which are relevant for academic achievement in adolescence. In addition, the aim of the research is also to determine potential differences with regard to the respondents’ gender. The sample included 350 adolescents, aged between 14 and 16 years (M=15.2), matched for their intelligence quotient, from different towns in Serbia. The following instruments were used – the Digit Span Test, Digit Symbol-Coding, the Trail Making Test, the Stroop Test, the Concentration Achievement Test (for measuring the components of attention), Raven’s Progressive Matrices (as a measure of intelligence). The results indicate that academic achievement is highly significantly associated with a certain configuration of components of the function of attention (goal-oriented selectivity, resistance to distractions, attention maintenance and concentration), and that the performance of students with poor academic achievement differs significantly from the performance of students with better academic achievement (p < 0.01). The results imply that the academic achievement or failure of adolescents cannot be interpreted without taking into account the characteristics of their attention. In addition, the results also indicate the necessity to establish an educational program with an aim to encourage the development of the assessed components of attention, in order for adolescents to attain academic achievements adequate to their intellectual capabilities.
Keywords: school performance of adolescents; self-regulation in learning; goal-oriented behavior; attentional control functions